Depletion of Platelet Amine Storage Granules by the Antithrombotic Agent, Suloctidil - Mills, David C. B.; Macfarlane, Donald E. (Thrombosis and Haemostasis, 1977)
Suloctidil, a compound with antithrombotic properties in animal models, causes depletion of human platelet serotonin stores during 1–5 hr incubation with platelet-rich plasma in vitro. This effect is not attended by leakage of cytoplasmic nucleotides or by alterations in cyclic AMP metabolism, malondialdehyde production or energy balance. 5HT uptake was also inhibited but uptake of adenine was not. 5HT released by suloctidil appeared in the supernatant as oxidation products, though the amine also accumulated when re-uptake was blocked by imipramine.